Extramedullary tanycytic ependymoma of the lumbar spinal cord - Dong Ja Kim (Yeungnam University Journal of Medicine, 2020)
Tanycytic ependymoma is a rare variant of ependymoma that commonly affects the cervical and thoracic spinal cord. It usually arises as intramedullary lesions, and extramedullary cases are extremely rare. We report a case of a 44-year-old woman who was diagnosed with tanycytic ependymoma in her lumbar spine at level 2-3. The tumor mass developed in an intradural extramedullary location. Histopathologically, tanycytic ependymoma can be misdiagnosed as schwannoma or pilocytic astrocytoma. Immunohistochemical findings such as strong positivity for glial fibrillary acidic protein, perinuclear dot-like positive patterns for epithelial membrane antigen, and focal positivity for S100 protein are helpful in diagnosing tanycytic ependymoma. It is important to be aware of this rare tumor to ensure appropriate patient management and accurate prognosis.